Ultrasonographic examination of the maturational effect of maternal vitamin D use on fetal clavicle bone development - Fatma Ozdemir; Banu Acmaz; Fatma Latifoglu; Sabahattin Muhtaroglu; Nefise Tanrıdan Okcu; Gokhan Acmaz; Iptisam Ipek Muderris (BMC Medical Imaging)
Abstract Aim This study aimed to evaluate the effect of maternal vitamin D use during intrauterine life on fetal bone development using ultrasonographic image processing techniques. Materials and methods We evaluated 52 pregnant women receiving vitamin D supplementation and 50 who refused vitamin D supplementation. Ultrasonographic imaging was performed on the fetal clavicle at 37–40 weeks of gestation. The fetal clavicle images were compared with adult male clavicle images. The texture features obtained from these images were used for analysis. Results No difference was observed in bone formation and destruction markers between the two groups. However, the texture analysis of ultrasonographic images revealed similarities in the characteristics of fetal clavicles in pregnant women receiving vitamin D supplementation and those of adult male clavicles. Conclusions Vitamin D supplementation in pregnancy has significant positive effects on fetal bone maturation besides contributing to maternal bone health. Texture feature analyses using ultrasonographic images successfully demonstrated fetal bone maturation.